2019
DOI: 10.1002/etc.4556
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicities of Neonicotinoids to Nymphs of the Common New Zealand Mayfly Deleatidium spp.

Abstract: Neonicotinoid insecticides have been shown to have high chronic toxicity relative to acute toxicity, and therefore short‐term toxicity tests ≤96 h in duration may underestimate their environmental risks. Among nontarget aquatic invertebrates, insects of the orders Diptera and Ephemeroptera have been found to be the most sensitive to neonicotinoids. To undertake a more accurate assessment of the risks posed by neonicotinoids to freshwater ecosystems, more data are needed from long‐term tests employing the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Two of them used imidacloprid and the others thiamethoxam; data from another test could not be used (Table S1). The same finding applies to two tests using imidacloprid: one on the amphipod Gammarus pulex [34] and another on the midge Chironomus riparius [35]. A further test using thiacloprid on the caddisfly Notidobia ciliaris suggests the same pattern, as indicated by n = 0.91 despite the poor fit of the model to the data (r 2 = 0.47) [9].…”
Section: Aquatic Organismsmentioning
confidence: 63%
“…Two of them used imidacloprid and the others thiamethoxam; data from another test could not be used (Table S1). The same finding applies to two tests using imidacloprid: one on the amphipod Gammarus pulex [34] and another on the midge Chironomus riparius [35]. A further test using thiacloprid on the caddisfly Notidobia ciliaris suggests the same pattern, as indicated by n = 0.91 despite the poor fit of the model to the data (r 2 = 0.47) [9].…”
Section: Aquatic Organismsmentioning
confidence: 63%
“…The present study, however, contrasts earlier studies reporting a reduction in molting rate, for instance, in cladoceran Daphnia magna (Qi et al 2013 ) or the mayfly Deleatidium spp. (Macaulay et al 2019 ) at higher concentrations of other neonicotinoids, namely guadipyr, imidacloprid, thiamethoxam and clothianidin. These contrasting effects point towards species- or neonicotinoid-specific effects in molting requiring further research to uncover the underlying mechanisms.…”
Section: Resultsmentioning
confidence: 97%
“…Clothianidin and imidacloprid depicted persistent toxicity impact on Deleatidium nymphs with LC 50 at 28 d as 1.36 and 0.28 ppb, respectively, with thiamethoxam being lowest in toxicity with 28 d LC 50 > 4 ppb. The molting of mayfly was negatively affected by imidacloprid (2 of 4 weeks), thiamethoxam (1 of 4 weeks) and clothianidin (3 of 4 weeks) [52]. Further in an acute and chronic toxicity study with imidacloprid exposure to freshwater arthropods, it was observed that caddisfly and mayfly species were utmost sensitive to imidacloprid exposures in short-term, whereas, mayflies were most sensitive to imidacloprid (long-term).…”
Section: Toxicity Of Neonicotinoids Towards Aquatic Invertebratesmentioning
confidence: 95%